The Good Christian Ruler in the First Millennium : Views from the Wider Mediterranean World in Conversation. - Forness, Philip Michael. (Millennium-Studien / Millennium Studies, 2021)
Millennium pursues an interdisciplinary approach transcending historical eras. The international editorial board and the advisory board represent a wide range of disciplines - contributions from art and literary studies are just as welcome as historical, theological and philosophical disciplines; contributions on Latin and Greek cultures just as welcome as on Oriental cultures.